Kajian Sensitifitas Komponen Biaya dan Tarif Pelabuhan Penyeberangan Dengan Model Dinamis - Siahaan, L Denny (Warta Penelitian Perhubungan, 2011)
Tiie price of crude oil in worldwide has fluctuating and giving as the result instabilization of production cost for industry, both service and manufacture industries. Government planning to decrease and even revoke the subsidy of gasoline is going to give domino effects for public and industry. The operator of Jerry transport therefore needs to anticipate the dynamic changes of price component then recalculate tlie price. Means, whereas the price may still cover the cost flu ctuation otherwise propose for increasing the price in order to give profit to the company. n zere are several scenarios in evaluating the existing price and it changes.Keywords : cost, price and dynamic model